Review of Istanbul - Sevim Sabriye Kalyoncu (International Institute of Islamic Thought, 2001)
With the picture of the city's skyline on its cover revealing the close proximity of the golden arches of a McDonalds to the dome and minaret of a mosque, this book automatically takes on the assumed conflict between Islam and the West as the backdrop to its discussion of the globalization of Istanbul. Recognizing globalization as the current paradigm of social change for third world countries disillusioned by the failure of modernization, Keyder does describe Istanbul as a global city, but more so in the sense of an historical location of opposition than a truly "important node in the*global economy." He emphasizes that the city has experienced "a different kind of economic globalization," with the typical global-city perspective failing to explain its evolution and Present-day conflicts. Not only does corruption run rampant, but defensive, localist attitudes also prevail in regards to issues related to the cultural change associated with globalization. Thus, while Istanbul is recognized as having the potential for becoming a global city, this potential, generally remains unfulfilled ...